The Republican Aventine and Rome's social order - Mignone, Lisa (University of Michigan Press, 2016)
"The Republican Aventine and Rome's Social Order is about one hill in particular, the Aventine, and its segregation from and integration into the residential fabric of Rome. My chronological focus is the Roman Republic, with studies peering into the Augustan principate. Throughout the text, all dates are BCE unless otherwise noted, and the title's reference to Roman social order reflects this monograph's twin themes: the plebs and urban stability. First, this book destabilizes the long-standing scholarly tradition that the Aventine was the citadel and headquarters for Rome's politically vibrant plebs. Second, it demonstrates that the development of the Aventine as a region mirrors the overall evolution of the urbs. The caput mundi was characterized by an extraordinary degree of socioeconomic integration, and the book concludes by proposing that this transurban heterogeneity may have contributed to the city's relative tranquility up until the final decades of the republic. This book aims to offer a deeply textured reconstruction of the Aventine as a literary and conceptual construct, on the one hand, and as a physical space, on the other. The city map is intentionally blank. Though we know which monuments stood on the Aventine in the Republic, we do not know where they stood. The ruins that have been recovered remain anonymous or assigned amid great conjecture. This book is not a topographical manual or an archaeological survey guide. It does not seek to attach famous figures to known archaeological sites or to assign residents to a map. A flurry of recent and ongoing scholarship has made that sort of work possible. The publication of the Lexicon Topographicum Urbis Romae in particular ensures that Rome's cultural geography will remain a very fertile and dynamic field within classical studies. The contribution of this monograph is that it applies fresh, critical readings to the literary tradition, material culture, and comparative urban studies, to offer a new assessment of one of Rome's canonical hills and to theorize broadly about republican Rome's residential practices"--Preface.